Comparison of Treatment Approaches and Subsequent Outcomes within a Pulmonary Embolism Response Team Registry - Anthony J. Weekes; Ariana Trautmann; Parker L. Hambright; Shane Ali; Angela M. Pikus; Nicole Wellinsky; Kelly L. Goonan; Sarah Bradford; Nathaniel S. O’Connell (Critical Care Research and Practice)
Objectives. To characterize the association between pulmonary embolism (PE) severity and bleeding risk with treatment approaches, outcomes, and complications. Methods. Secondary analysis of an 11-hospital registry of adult ED patients treated by a PE response team (August 2016–November 2022). Predictors were PE severity and bleeding risk. The primary outcome was treatment approach: anticoagulation monotherapy vs. advanced intervention (categorized as “immediate” or “delayed” based on whether the intervention was received within 12 hours of PE diagnosis or not). Secondary outcomes were death, clinical deterioration, and major bleeding. Results. Of the 1832 patients, 139 (7.6%), 977 (53.3%), and 9 (0.5%) were classified as high-risk, intermediate-high, intermediate-low, and low-risk severity, respectively. There were 94 deaths (5.1%) and 218 patients (11.9%) had one or more clinical deterioration events. Advanced interventions were administered to 86 (61.9%), 195 (27.6%), and 109 (11.2%) patients with high-risk, intermediate-high, and intermediate-low severity, respectively.Major bleeding occurred in 61/1440 (4.2%) on ACm versus 169/392 (7.6%) with advanced interventions (p <0.001): bleeding withcatheter-directed thrombolysiswas 19/145 (13.1%) versus 33/154(21.4%) with systemic thrombolysis,p= 0.07. High risk was twice as strong as intermediate-high risk for association with advanced intervention (OR: 5.3 (4.2 and 6.9) vs. 1.9 (1.6 and 2.2)). High risk (OR: 56.3 (32.0 and 99.2) and intermediate-high risk (OR: 2.6 (1.7 and 4.0)) were strong predictors of clinical deterioration. Major bleeding was significantly associated with advanced interventions (OR: 5.2 (3.5 and 7.8) for immediate, 3.3 (1.8 and 6.2)) for delayed, and high-risk PE severity (OR: 3.4 (1.9 and 5.8)). Conclusions. Advanced intervention use was associated with high-acuity patients experiencing death, clinical deterioration, and major bleeding with a trend towards less bleeding with catheter-directed interventions versus systemic thrombolysis.